"DEVONI FONIY" - A MASTERPIECE (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes Alisher Navoi's adaptations to Amir Khusrav Dehlavi's ghazals in the collection "Devoni Foniy". It demonstrates the artistic significance of the adaptation tradition carried out by Navoi, his ideological and methodological approaches, as well as the creative connections between the two great poets. The example of adaptation reveals Navoi's place in Uzbek literature, its interconnection with the traditions of great Persian-Tajik literature, the culture of literary dialogue, and his attitude to spiritual heritage. The article serves to shed light on the scientific and practical significance of literary adaptations, and to provide a deeper understanding of Navoi's literary worldview through his practical work.